Contaminação de solo de áreas de lazer por ovos de Toxocara spp em regiões central e periurbana de Mirante do Paranapanema, São Paulo, Brasil - Dias, Aparecida Pereira (2007)
In order to evaluate the enviromental contamination by Toxocara spp eggs in public areas in Mirante do Paranapanema, São Paulo, Brazil, and to compare the frequencies in central areas (area 1: six parks) and periurban (area 2: seven parks), 250g of soil were collected from five different sites from 13 public parks. Two aliquots of 10 g were analyzed using the centrifuge-fluctuation technique with sodium nitrate (d= 1,200 g/cm3). The contamination was observed in 76.9% of parks, being all the periurban parks contaminated (7/7). On other hand, it wqas registered the presence of Toxocara spp eggs in 50% (3/6) of the central places (p<0.05). From recovered eggs 33.3% were available, and 15.15% had moving larvae. The results pointing the parks of Mirante do Paranapanema as a source of infection for the human population to toxocariasis.